Many Faces of Ni3Bi2S2: Tunable Nanoparticle Morphology via Microwave-Assisted Nanocrystal Conversion - Roslova, Maria; Van Den Broek, Wouter; Isaeva, Anna; Doert, Thomas; Ruck, Michael (Crystal Growth and Design, 2018)
Several combinations of the microwave-assisted polyol route and conversion chemistry techniques were exploited to access the bimetallic sulfide Ni3Bi2S2 with a variety of morphological features. First, Bi2S3 microstructures can be converted into Ni3Bi2S2 at 240 °C; the precursor's rod-like shape and size pertain to the final product. Second, round Ni3Bi2S2 particles can be obtained directly from a presynthesized NiBi intermetallic precursor; the resultant submicron size particles agglomerate and thus differ from the starting alloy's shape. Third, microwave reflux of bismuth nitrate and nickel acetate solution in ethylene glycol in the presence of thiosemicarbazide can be employed to produce Ni3Bi2S2 with a peculiar flower-like morphology. The presence and the decisive role of the in situ generated NiBi intermediate are unraveled, confirming that the reaction proceeds via transformation of solid rather than via a solution-dissolution process. NiBi nanoparticles preconfigure the Ni3Bi2S2 product morphology in a wide range of pH values. In turn, the pH value is found to be a key factor that determines the type of impurities accompanying the Ni3Bi2S2 ternary phase. At pH ≈ 4 bismuth precipitates as a main side-phase, while pH ≈ 12 favors the formation of NiS impurity.
CRIS-Team Scopus Importer:2022-04-14